Antitrypanosomal activities of selected medicinal plants - Dyary, Hiewa O.; Abdul Kadir, Arifah; Kumar Sharma, Reuben Sunil; Abdullah, Rasedee; Md. Sukari, Mohd Aspollah; Zakaria, Zainul Amiruddin; Ahmad, Zuraini; Somchit, Muhammad Nazrul (2012)
The aqueous and ethanolic extracts from four medicinal plants namely Acanthus ilicifolius, Aquilaria malaccensis, Goniothalamus tapis, and Maesa ramentacea, were tested in vitro against Trypanosoma evansi, a hemoprotozoan parasite causing surra in a vast variety of domesticated and wild animals. The antitrypanosomal activity was evaluated by calculating median inhibitory concentration (IC50), the concentration that gives half maximal growth of the trypanosomes, of the plant extracts. Goniothalamus tapis ethanolic extract showed the most potent antitrypanosomal activity with an IC50 value of 7.6 ± 1.6 μg ml-1. The other extracts scored IC50 values ranging from 36.2 ± 1.3 μg ml-1 to 314.1 ± 37.1 μg ml-1.